PERLUASAN REGRESI COX DENGAN PENAMBAHAN PEUBAH TERIKAT-WAKTU - DEWIYANTI, LUH PUTU ARI; SUCIPTAWATI, NI LUH PUTU; SUMARJAYA, I WAYAN (E-Jurnal Matematika, 2014)
The aim of this study is to model job hunting period in Bali in 2012 using Extended Cox model. Previous study concluded that household status and age variables were not significantly influenced the job hunting period. However, previous study on factors that influence job waiting suggests that both variables should play important role in determining the waiting time for job hunters. Thus incorporating time-dependent covariates into model is necessary. After incorporating time-dependent covariates we found that age with time-dependent covariate is significant.
Keywords: extended Cox model; job hunting period; survival analysis